Low Carbohydrate Availability Reduces Power Output at the Moderate-to-Heavy Transition, Impairs Efficiency, and Increases Median Power Frequency During Cycling in Females - Main, Evana; Yoon, SangHoon; James, Samuel; Mellor, Kimberley; Brick, Matthew; Leigh, Warren; Maunder, Ed (Springer, 2026)
PURPOSE: Carbohydrate availability is reduced during prolonged exercise, and this may contribute to the loss of power output at the intensity domain transitions. The aim of this study was to investigate the effects of lowered carbohydrate availability on power output at intensity domain transitions, muscle activation, and gross cycling efficiency in endurance-trained female cyclists. METHODS: Nine well-trained female cyclists completed a randomised, counterbalanced crossover study consisting of two conditions. Participants completed an incremental cycling test and three-minute all-out test, preceded by glycogen-depleting exercise ~ 24 h beforehand and subsequent carbohydrate ingestion of either ≥ 9 g kg-1 (HIGH) or ≤ 1 g kg-1 (LOW). RESULTS: Power output at the first ventilatory threshold was reduced in LOW (133 ± 24 vs. 152 ± 28 W, ∆ - 19 ± 14 W, P = 0.011), with no between-trial difference in power output at the lactate threshold. Gross cycling efficiency during submaximal cycling was reduced in LOW (P = 0.003). Electromyographic median power frequency of the vastus lateralis (P = 0.025) and vastus medialis (P = 0.007) was higher in HIGH during submaximal cycling, with no between-trial differences in electromyographic amplitude. There was no between-trial difference in end-test power output during the three-minute all-out test. CONCLUSION: These data suggest lowered carbohydrate availability reduced power output at the moderate-to-heavy transition, possibly due to increased recruitment of higher-threshold motor units to compensate for glycogen-depleted fibres, impairing gross cycling efficiency. These data suggest that carbohydrate availability is likely important in 'durability' of the moderate-to-heavy intensity transition.
Keywords: Carbohydrate availability; Cycling efficiency; Female cyclists; Fibre recruitment; Intensity domain transitions; 1106 Human Movement and Sports Sciences; Sport Sciences; 3202 Clinical sciences; 3208 Medical physiology; 4207 Sports science and exercise